Educação em direitos humanos: caminhos para a efetivação da democracia e dos direitos humanos e o papel da Defensoria Pública - Cruz, Rafael Rocha Paiva (2014)
The purpose of this thesis is to analyze human rights education and its relationships with the realization of human rights and democracy, with emphasis on processes of discrimination and exclusion, as well as the role of Legal Services in the aforementioned field. This analysis is justified by the currency and importance of the subject in both national and international settings, and its relationship with constitutional principles and objectives. The hypothesis is that human rights education can contribute significantly to the realization of democracy and human rights, including in cases involving discrimination and exclusion, and that Legal Services have an important role therein. First, the meanings and main issues pertaining to education, human rights and democracy are analyzed in association with the subject are analyzed in a historical-critical study. Then, the several aspects of human rights education and applicable national and international regulations are examined. Finally, this work demonstrates the significant capabilities of human rights education to contribute to human rights and democracy realization, particularly in favor of discriminated and excluded individuals and groups, as well as the relevant role of Legal Services in this field, thus confirming the thesis